Additive benefits of long-chain n-3 polyunsaturated fatty acids and weight-loss in the management of cardiovascular disease risk in overweight hyperinsulinaemic women. - Krebs, J; Browning, L; McLean, N; Rothwell, J; Mishra, G; Moore, C; Jebb, SA (2006)
BACKGROUND: Obesity, inflammation, insulin resistance and cardiovascular disease (CVD) risk are inter-related. Both weight-loss and long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) are independently known to reduce metabolic risk, but the combined effects are unclear. OBJECTIVE: This study examines whether addition of LC n-3 PUFA to a low fat/high carbohydrate weight-loss programme results in greater improvements in inflammation, insulin sensitivity and CVD risk, than weight-loss alone. DESIGN: One hundred and sixteen overweight insulin-resistant women entered a 24-week randomised intervention study. Thirty-nine women were randomised to a weight-loss programme, with LC n-3 PUFA (WLFO), 38 to a weight-loss programme with placebo oil (WLPO), and 39 to receive placebo oil, with no weight-loss programme (control). RESULTS: Ninety-three women completed the study (35 WLFO, 32 WLPO and 26 control), with significant weight-loss in WLFO (10.8+/-1.0%) and WLPO (12.4+/-1.0%) compared to the control group (P<0.0001). The WLFO, but not WLPO or control group, showed significant increases in adipose tissue LC n-3 PUFA (0.34+/-0.20 vs 0.17+/-0.10 and 0.16+/-0.10 %DHA, P<0.0001). Weight-loss showed significant improvements in insulin sensitivity (P<0.001), lipid profile (triglycerides P<0.05) and inflammation (sialic acid P<0.05). Time*group effects showed significant decreases in triglycerides (P<0.05) and increases in adiponectin (P<0.01) with LC n-3 PUFA, in the WLFO vs WLPO groups. CONCLUSIONS: Weight-loss improved risk factors associated with CVD, with some additional benefits of LC n-3 PUFA on triglycerides and adiponectin. Given the current low dietary intake of LC n-3 PUFA, greater attention should be given to increase these fatty acids in the treatment of obesity.